"Just The Way We've Always Done It": Who Shapes The New Normal for Academic Libraries? - McLay Paterson, Amy (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2022)
In March and April of 2021, my co-investigators and I conducted semi-structured interviews with academic librarians across Canada about their work during the COVID-19 pandemic, which included their thoughts about going “back to normal.” Most participants were resistant to returning to the “old normal” without myriad changes inspired by the COVID-necessitated adaptations. However, there were concerns raised about whether or not their ideas would be implemented or even heard by their administrations. Additionally, many participants felt caught between proving their value through productive (and measurable) labour and the care-work that felt necessary and pressing but was not externally validated. This paper highlights the need for refocusing on building library collegial governance structures that include all library workers. As well, there is indication that the COVID-19 pandemic presents a unique opportunity to do so, as, removed from the “sacred space” (Ettarh 2018) of the library building, participants showed resistance to the austerity narratives typically invoked during a crisis. Embodying our values starts with establishing and building on shared library governance structures. If the changes inspired by COVID are to come to pass, then our vision of care and relationship-building must be inclusive to our own workers, to harness our collective power to build a future that works for everyone.